MAKNA UPACARA MAMONGOTI BAGAS PADA MASYARAKAT ETNIS BATAK TOBA DI KELURAHAN DATARAN TINGGI KECAMATAN BINJAI TIMUR - Malau, Waston; Triana Munte, Monika (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2024)
This research aims to identify the background to the emergence of the mamongoti bagas ceremony, find out the process of carrying out the mamongoti bagas ceremony and the meaning of the mamongoti bagas ceremony among the Toba Batak ethnic group on Jalan Ikan Arwana, Highland Highlands District. The type of research used is qualitative research with a descriptive approach. This research uses the theory of symbolic meaning in the mamongoti bagas ceremony. The data collection techniques used in this research were through interviews and documentation. The intended research informants were traditional and community leaders. Data analysis techniques are carried out through data reduction, data presentation and data verification. The results of this research reveal that the traditional mamogoti bagas ceremony is a ceremony when a family wants to occupy a house that has just been built or purchased.Â  This ceremony is carried out by inviting hula-hula, bones and other relatives to pray and worship in the new house. Apart from that, people carry out the mamongoti bagas ceremony as a prayer of hope for safety, asking for good fortune, happiness and smoothness in work